Relative performance evaluation, sabotage and collusion - Bloomfield, Matthew J.; Marvão, Catarina; Spagnolo, Giancarlo (Journal of Accounting and Economics, 2023)
We examine whether the potential for costly sabotage is a deterrent to firms' use of relative performance evaluation (“RPE”) in CEO pay plans. We exploit illegal cartel membership as a source of variation in the potential for costly sabotage and document that firms are more likely to use RPE if they are currently cartel members. Moreover, firms frequently drop RPE from their CEOs’ pay plans immediately after their cartels are detected, dissolved and punished. We further provide suggestive evidence that the potential for costly sabotage explains these patterns; cartel membership severs the empirical association between RPE and competitive aggression.